2007
DOI: 10.1021/es070769c
|View full text |Cite
|
Sign up to set email alerts
|

Debromination of Decabrominated Diphenyl Ether by Resin-Bound Iron Nanoparticles

Abstract: Nanoscale zerovalent iron, n-ZVI, was found to be highly effective in reductively debrominating decabromodiphenyl ether (BDE209) at ambient conditions and without the catalysis of noble metals. A method was developed to immobilize n-ZVI particles on a cation-exchange resin. The n-ZVI coated resin was then mixed with BDE209 in a water/ acetone (1:1) solution, and the reaction was allowed to proceed for up to 10 days. The first-order rate constant of BDE209 disappearance was estimated to be 0.28 - 0.04 h(-1). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(137 citation statements)
references
References 25 publications
6
128
1
2
Order By: Relevance
“…However, initially, reaction times were very long (5Á40 days). Later, Li has forwarded the use of nanosized iron particles bound on cation-exchange resin (27). The reaction rate of the debromination was reported to be far superior to those using micrometersized Fe particles (26).…”
Section: Introductionmentioning
confidence: 99%
“…However, initially, reaction times were very long (5Á40 days). Later, Li has forwarded the use of nanosized iron particles bound on cation-exchange resin (27). The reaction rate of the debromination was reported to be far superior to those using micrometersized Fe particles (26).…”
Section: Introductionmentioning
confidence: 99%
“…Unidentified PBDEs can be presumptively identified by comparing relative retention time and order with those reported in the retention studies of non-BDEs including BDE207 and BDE208 [9,23], and octa-BDEs [24][25][26][27]. For BDE209 quantitative analysis, the method detection limit (MDL) was 0.01 µg$L -1 and the method recovery was greater than 80%.…”
Section: Methodsmentioning
confidence: 99%
“…1). The debromination of BDE-209 in the presence of zerovalent iron microparticles (Zhuang et al 2010) and resin-bound iron nanoparticles (Li et al 2007) also followed pseudo-first-order kinetics, with rate constants of 9.79×10 −5 min −1 (0.14 day −1 ) and 4.7×10 (Su et al 2014). The degradation behaviors of different halogenated compounds might vary in ways that are strongly dependent on the halogen substituents and chemical properties of the compounds.…”
Section: Kinetics Studymentioning
confidence: 97%
“…Five octa-BDE peaks were found, and they were identified as , again from the available standards. It has been reported that more than five major octa-BDE congeners are rarely detected by GC after BDE-209 has been degraded, regardless of which medium the reaction has been performed in (Li et al 2007). Indeed, the same conclusion could be drawn in the present study.…”
Section: Analysis Of the Degradation Productsmentioning
confidence: 99%
See 1 more Smart Citation